Induction of labour versus expectant management in women with premature rupture of membranes between 34 to 37 weeks of gestation - Ferdous, Afroza; Chowdhury, Shahanara; Akter, Rowshan (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: PROM; preterm labour; chorioamnionitis DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9106 JCMCTA 2011; 22(1): 15-19